Infrastructure projects in Indonesia and the Philippines : A comparative study. - Gek, Yin Teen. (2008)
In recent years, the widening gap between economic growth and government-financed infrastructure in Indonesia and the Philippines has led to new government policies that encouraged the participation of the private sector in infrastructure development. Among the various methods of private sector participation the Build-Operate-Transfer (BOT) method and its variants have been popular in these countries. This study has identified some factors (concerns) that are recognized to be likely to result in the success or failure of a BOT project.